A crossover trial comparing contamination of healthcare personnel during removal of a standard gown versus a modified gown with increased skin coverage at the hands and wrists. (22nd August 2019) - Hajar, Zeina; Mana, Thriveen S. C.; Tomas, Myreen E.; Alhmidi, Heba; Wilson, Brigid M.; Donskey, Curtis J.
Abstract: In a crossover trial, a gown designed to increase skin coverage at the hands and wrists significantly reduced contamination of personnel during personal protective equipment (PPE) removal, and education on donning and doffing technique further reduced contamination. Simple modifications of PPE and education can reduce contamination during PPE removal.